2015
DOI: 10.15376/biores.10.2.2783-2796
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Mechanical, and Physicochemical Behaviours of Alkali Pre-treated Oil Palm Stalk Fibres

Abstract: The effect of alkali pre-treatment (sodium hydroxide, NaOH) on the microstructural, mechanical, and chemical composition of oil palm stalk fibres (OPSF) is reported for future bioconversion processes. The OPSF was pre-treated with various concentrations of NaOH (5, 10, 20, 30, and 40% w/v). Scanning electron microscopy analysis revealed that 5% w/v alkali concentration caused complete removal of silica bodies and waxy layers, whereas pronounced degradation of the fibres occurred at 40% w/v NaOH concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Figure 4 shows images of the different stages that were involved in the extraction process of SCMC, where a comparison with COMM1 and COMM2 was analyzed by SEM. Similarly, Xiang et al (2015) reported that excessive lignin and waxes were apparent on the raw OPEFB stalk fibre.…”
Section: Ftir Analysismentioning
confidence: 95%
“…Figure 4 shows images of the different stages that were involved in the extraction process of SCMC, where a comparison with COMM1 and COMM2 was analyzed by SEM. Similarly, Xiang et al (2015) reported that excessive lignin and waxes were apparent on the raw OPEFB stalk fibre.…”
Section: Ftir Analysismentioning
confidence: 95%
“…Compared with DG1, the peak height of DG6 increased at 3427 cm − 1 , indicating an increase in hydrogen-bonded association -OH with cellulose, meaning an increase in the fiber water absorption. e main reasons for the increase of water absorption of the DG6 fiber are as follows: NaOH solution hydrolyzes the waxy layer on the surface of straw fibers into higher fatty acids and higher fatty alcohols and then destroys the waxy layer on the surface [50,51]; when the metal hydrated ions in the NaOH solution enter the cellulose and interact with hydrogen bonds on the cellulose chain, it destroys some crystalline region of cellulose, decreasing the crystallinity of cellulose [52,53]. On the other hand, the absorption peak of DG6 sees a significant increase at 2918 cm − 1 corresponding to DG1, but disappears at 1516 cm − 1 and 1242 cm − 1 and diminishes at 1057 cm − 1 , indicating that the content of cellulose increased, the content of lignin decreased, and the crystallinity of the fibers increased after modification with the NaOH solution.…”
Section: Effect Of Modification Methods On Chemical Structure Of Stramentioning
confidence: 99%
“…The filler used was oil palm mesocarp fibres (OPMF) obtained from Besout Palm Oil Mill (Sungkai, Perak, Malaysia), which were kept in a controlled environmental of -20 °C. The fibres were washed to remove oil residues and dried at 105 °C for 24 h until moisture content reached below 5% (Xiang et al 2015). Regarding the treated sample used in degree of grafting (DOG) analysis, OPMF were treated with 500 mL of sodium hydroxide solution (NaOH) at constant concentrations of 5% (w/v) of fibre to (NaOH) ratio of 1:10 (g/mL), as described by Xiang et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The fibres were washed to remove oil residues and dried at 105 °C for 24 h until moisture content reached below 5% (Xiang et al 2015). Regarding the treated sample used in degree of grafting (DOG) analysis, OPMF were treated with 500 mL of sodium hydroxide solution (NaOH) at constant concentrations of 5% (w/v) of fibre to (NaOH) ratio of 1:10 (g/mL), as described by Xiang et al (2015). OPMF were soaked in NaOH solution for 30 min at room temperature and then autoclaved at 121°C, 15 psi for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation